The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3ta01196h
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium plasma-assisted dry reforming of methane over shape-controlled CeO2 supported ruthenium catalysts

Abstract: In this report, CeO2 and SiO2 supported 1 wt% Ru catalysts were synthesized and studied for dry reforming of methane (DRM) by introducing non-thermal plasma (NTP) in a dielectric barrier...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The application of CeO 2 can enhance the metal–ceria interaction and suppress carbon deposition through the redox cycles of Ce 3+ and Ce 4+ under a reductive atmosphere during the DRM reaction. 184,185 Previous experimental and theoretical studies showed that ceria-supported catalysts had strong metal–support interaction, which greatly improved the catalyst stability. In addition, the redox property of the catalyst is also affected by the morphology of Ce.…”
Section: Physical and Chemical Properties Of Co-based Catalysts For Drmmentioning
confidence: 99%
“…The application of CeO 2 can enhance the metal–ceria interaction and suppress carbon deposition through the redox cycles of Ce 3+ and Ce 4+ under a reductive atmosphere during the DRM reaction. 184,185 Previous experimental and theoretical studies showed that ceria-supported catalysts had strong metal–support interaction, which greatly improved the catalyst stability. In addition, the redox property of the catalyst is also affected by the morphology of Ce.…”
Section: Physical and Chemical Properties Of Co-based Catalysts For Drmmentioning
confidence: 99%
“…According to reports, integrating energy levels into heterogeneous structures of composite semiconductor photocatalysts can effectively suppress light-induced recombination of charge carriers. The formation of heterogeneous structures can significantly improve the spatial charge separation effect, prolong the lifetime of charge carriers, and thus greatly enhance the photocatalytic performance . To achieve such a photoanode system, an n-type metal oxide semiconductor is commonly employed due to its ability to perform the anodic OER reaction without semiconductor degradation in highly oxidizing electrochemical environments. , Cerium oxide (CeO 2 ) has been proven to exhibit excellent photocatalytic performance in the degradation of various organic dye pollutants, owing to its high oxygen storage capacity, catalytic reactions involving Ce 3+ /Ce 4+ ion pairs, environmental friendliness, and cost-effectiveness .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they can immobilize and convert polysulfides, thus reducing their migration and alleviating capacity degradation. 45,46,49 When cerium is introduced into Li 2 S-P 2 S 5 (LPS), the defect structure and/or conentration of the material can be modified, thereby enhancing the migration of Li + ions, resulting in an improvement in the ionic conductivity of the material. It is believed that a significant part of this enhancement can be attributed to the introduction of additional mobile charge carriers and the optimization of the Li-ion diffusion pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The cerium ions (Ce 4+ /Ce 3+ ) can act both as redox mediators and as redox catalysts in Li‐S battery due to their variable oxidation states. As a result, they can immobilize and convert polysulfides, thus reducing their migration and alleviating capacity degradation 45,46,49 . When cerium is introduced into Li 2 S‐P 2 S 5 (LPS), the defect structure and/or conentration of the material can be modified, thereby enhancing the migration of Li + ions, resulting in an improvement in the ionic conductivity of the material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation